2013
DOI: 10.1039/c3mt20264j
|View full text |Cite
|
Sign up to set email alerts
|

d-Histidine and l-histidine attenuate zinc-induced neuronal death in GT1-7 cells

Abstract: Although zinc (Zn) is an essential trace element, excess Zn causes neuronal death following transient global ischemia and plays a central role in the pathogenesis of vascular-type dementia. In this study, we developed a rapid and convenient screening system for substances that prevent Zn-induced neurotoxicity by using GT1-7 cells (immortalized hypothalamic neurons), with the aim of identifying a treatment for vascular-type dementia. Among tested, we found a protective substance in the extract of round herring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 33 publications
0
56
0
Order By: Relevance
“…25 Here, GT1-7 cells were simultaneously treated with Zn and carnosine, His, or anserine. 25 Here, GT1-7 cells were simultaneously treated with Zn and carnosine, His, or anserine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Here, GT1-7 cells were simultaneously treated with Zn and carnosine, His, or anserine. 25 Here, GT1-7 cells were simultaneously treated with Zn and carnosine, His, or anserine.…”
Section: Resultsmentioning
confidence: 99%
“…Mellon et al originally developed GT1-7 cells by genetically targeting tumorigenesis in mouse hypothalamic neurons. 25 As the disruption of Ca 2+ homeostasis may be involved in Zn-induced neurotoxicity, we focused on the implications of these factors in the protective activity of carnosine. In addition, GT1-7 cells either lack or express low levels of ionotropic glutamate receptors and do not show glutamate toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we investigated the alterations in gene expression during Zn-induced neurotoxicity with a DNA microarray and RT-PCR [42]. The expression of several genes, including metal-related genes, such as metallothionein ( MT ) -1 , MT-2 , and the Zn transporter 1 ( ZnT-1 ) were induced by Zn exposure.…”
Section: Zinc and Vascular-type Dementiamentioning
confidence: 99%
“…(see Zn in Figure 5). Furthermore, our investigation into the changes in gene expression during Zn-induced neuronal death revealed an upregulation of several genes, including ER stress-related genes [growth-arrest DNA damage ( GADD ) 34 , GADD45 , and p8 ) and the Ca 2+ -related gene Arc (activity-related cytoskeleton protein) [42]. These findings are important considering the involvement of Ca 2+ homeostasis in Zn-induced neurotoxicity.…”
Section: Zinc and Vascular-type Dementiamentioning
confidence: 99%
“…We recently suggested that Ca dyshomeostasis may be involved in the mechanisms underlying Zn-induced neurotoxicity [51]. Zn-induced neuronal death revealed an upregulation of several genes, including metalrelated genes (metallothionein (MT)-1,MT-2, and the Zn transporter 1 (ZnT-1)), ER stress-related genes (growth-arrest DNA damage (GADD)34, GADD45, and p8), and the Ca 2+ -related gene Arc(activity-related cytoskeleton protein) [70]. These findings are significant, given the involvement of Ca 2+ homeostasis in Zn-induced neurotoxicity.…”
Section: Carnosine Inhibits Zinc-induced Neurodegenerationmentioning
confidence: 99%